Formas de fósforo em latossolo vermelho-escuro álico. 1- P-solúvel e P-Al - de Araújo, Nelson; Ferreira, Manoel Evaristo; Pereira, Gener Tadeu; Valério Filho, Walter Veriano (Eclética Química, 1990)
.